Relation of sleep and musculoskeletal disorders among workers: a systematic review - Zaheer, Dania; Munawar, Arooj; Ali, Sarwat (Journal of the Pakistan Medical Association, 2023)
Objective: To systematically review literature on the relationship of sleep with musculoskeletal disorders. Method: The systematic review was conducted after approval from the ethics review board of the University of Lahore, Lahore, Pakistan, and comprised search of relevant literature published from 2012 to 2020 on Web of Science, Latin America and the Caribbean Literature on Health Sciences and PakMedinet electronic databases. The key words used during the search included workers, musculoskeletal pain, insomnia, musculoskeletal diseases, pain and sleep disorders. outcome measures were the Nordic Musculoskeletal Questionnaire, Numerical Rating Scale, Musculoskeletal Complaint Severity Index, Epworth Sleepiness Scale, Bergen Insomnia Scale, Karolinska Sleepiness Questionnaire and the National Institute for Occupational Safety and Health score. PROSPERO CRD42021281084 Results: Of the 1,538 studies found, 13(0.8%) were reviewed. The relationship between pain and sleep was not found among studies but, sleep disturbances were found to be linked to MSK pain in various parts of the body among workers. Conclusion: Healthy lifestyle contributing to improvement in sleep quality and prevention of musculoskeletal pain should be considered in order to enhance the quality of life among workers. Systematic review registration: PROSPERO CRD42021281084 Key Words: Allied health personnel, Insomnia, Musculoskeletal pain, Musculoskeletal diseases, Pain, Sleep disorders.